Phenology of Terminalia chebula tree in the Dry Deciduous Forest of Cauvery Wildlife Sanctuary, Karnataka, Southern India - Kailash, B. R.; Harisha, R. P.; Siddappa, Setty R.; Kadirvelu, K.; Manimekalan, M. S.; Samrat, Abhishek (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted at Cauvery wildlife sanctuary, Karnataka, India from 2015 to 2019. This study intended to understand the periodic events in biological life cycles concerning changes in the timings of seasonal events. It includes leafing, flowering, and fruiting patterns among the selected tree species of Terminalia chebula Retz., which is an important non-timber forest product (NTFPs) species in the Cauvery wildlife sanctuary. A total of 32 adult individual trees, from two transects at different places were selected and were observed at thirty days intervals. It was observed that there was a species-specific phenological relationship between the deciduous period and the initiation of seasonal rainfall and warm periods. Leaf maturity peak was in August. Leaf fall activity was in January before the arrival of an intense dry period. The reproductive phenology like flowering, fruiting, and fruit obsession was significantly varied across the different seasons among the observed tree species. The majority of tree species (56%) revealed synchronous flowering with Leaf flush activity. The results indicate that Leafing (58%) and flowering phenology (75%) occur during the dry period before the onset of first rains and fruiting, fruit fall timing was in consequence to utilize the growing season. Thus, species specificity was recorded concerning flowering and fruiting and was found to be with the seasonal rainfall distribution and in turn soil moisture availability in the study area. The results of the study would help in better management of fruiting tree species in natural forests.